2017
DOI: 10.3390/su9061038
|View full text |Cite
|
Sign up to set email alerts
|

Technology Forecasting Using a Diffusion Model Incorporating Replacement Purchases

Abstract: Understanding the nature of the diffusion process is crucial for sustainable development of a new technology and product. This study introduces a replacement diffusion model that leads to a better understanding of the growth dynamics of a technology. The model operates in an environment with multiple competitors and overcomes the limitations of existing models. The model (1) consists of a diffusion model and an additional time series model; (2) separately identifies the diffusion of first-time purchases and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The first-time adoption occurs at the initial stage of the technology lifecycle, and consequently, repurchasing becomes a crucial factor in the diffusion of most technological products (Parker 1992). Therefore, the diffusion models have been modified to incorporate the notion of repeat purchasing (Mahajan et al 1983;Olson and Choi 1985;Danaher et al 2001;Singh et al 2012;Stummer et al 2015;Lee and huh 2017;Anand et al 2018).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The first-time adoption occurs at the initial stage of the technology lifecycle, and consequently, repurchasing becomes a crucial factor in the diffusion of most technological products (Parker 1992). Therefore, the diffusion models have been modified to incorporate the notion of repeat purchasing (Mahajan et al 1983;Olson and Choi 1985;Danaher et al 2001;Singh et al 2012;Stummer et al 2015;Lee and huh 2017;Anand et al 2018).…”
Section: Related Literaturementioning
confidence: 99%
“…In addition, the diffusion models for initial purchases have been improved upon to include replacement and repurchasing. Usually, the first-time buyers who have adopted the innovation at the starting of the diffusion life cycle may likely to repurchase the innovation over the long run (Olson and Choi 1985;Lee and Huh 2017). Moreover, the preferences of potential buyers may vary with the changing market dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified the factors affecting diffusion speeds and explaining variation in diffusion speeds for different innovations. Some of these studies have taken a static view of diffusing innovations and emphasized the effects of economic and social environment factors on diffusion speeds (Bayus, 1992;Cho et al, 2012;Griliches, 1957;Lee et al, 2017;Mansfield, 1961;1989;Olshavsky, 1980;Rogers, 1995;Van den Bulte, 2000). Meanwhile, there are theoretical studies noting that technological improvement also significantly affects the diffusion process (Chow, 1967;Davies, 1979;Ireland and Stoneman, 1986;Metcalfe, 1981;Rosenberg, 1976;Stoneman and Ireland, 1983;Stoneman, 2002) and empirical studies to provide evidence for this effect in some products such as computers, numerically controlled machine tools, semi-dwarf wheat, and telephones (Bagchi et al, 2008;Chow, 1967;Karshenas and Stoneman, 1993;Knudson, 1991;Stoneman and Toivanen, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Since the numerous information and knowledge exist all around our society and economy, consumers can easily gather and access their own customized information for buying goods and services. Moreover, amid the accelerated development of information and communication technologies (ICTs), the boundary of a market for goods and services is no longer limited in the off-line and online marketplaces, but it has extended to the mobile market [1][2][3]. In this situation, firms are required to establish new management strategies for their sustainable business development [4].…”
Section: Introductionmentioning
confidence: 99%
“…For that for the different types of innovation activities; also what are the relationships between the consulting environment of client firms and innovation activities via the role of CEOs and their institutional conditions for consulting projects; how do these relationships differ for the different types of innovation activities; how do the innovation activities affect the business performance through the consulting process and performance; which consulting factors have higher impact on the contribution to business performance; if so how do the factors affect the strategies for sustainable business development? Moreover, this paper has the following research purposes: (1) to build the consulting model framework, which will be used for establishing strategies for sustainable business development; (2) to analyze the relationships between consulting factors and consulting performance through innovation activities for finding the key variables in the model, which might affect the firms' business performance and the strategies for sustainable business development; (3) to provide and suggest implications for the sustainable growth of firms with regard of innovation ambidexterity.…”
Section: Introductionmentioning
confidence: 99%